Effectiveness intelligent building in Malaysian construction industry / Sabariah Sareh Saad - Saad, Sabariah Sareh (Faculty of Architecture, Planning and Surveying, 2008)
The essence of Building Management Systems and Intelligent Buildings is in the control technologies, which allow integration, automation, and optimization of all the services and equipment that provide services and manages the environment of the building concerned. Intelligent Buildings and Building Management Systems technologies contribute directly to the reduction in energy use in office building. In short, Intelligent Buildings and suitably applied Building Management Systems are good for the environment. The intention of this research is to study the effectiveness of intelligent building to users. The research also identifies the types of system in each building. The studies are based o three selected office building in Klang Valley. This research is also identifies the characteristics of intelligent building in each of building. In addition, the studies also identified the problem that has been arising for the system at the building. This research involved a qualitative methodology. The qualitative study was to examine the perceptions of the users about the satisfaction of system in intelligent building. 30 questionnaires were distributed to each case study (Putrajaya Convention Centre PCC), Pusat Tenaga Malaysia (PTM) Zero Energy Office Building (ZEO Building),and The Ministry of Energy, Water and Communications (MEWC) Low Energy Office (LEO Building)) and almost the same total of 90 respondents responded and returned for analysis. This survey was made possible with the help and permission from the operation management. Moreover this research also uses structured interview to get more detail information about intelligent building. In interview session, many differentiation and analogy of intelligent building can complete this research.